ANALISIS LIKUIDITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Hayat, Indra; Wage, Sunarto (LPPM Universitas Putera Batam, 2022)
The solvency ratio has a slightly related effect on the stock price, as the DER is greater than 1.67412 and has a significant value of 0.04 0.05. In addition, the f-test is 3.557> 3.17 and the significant value is 0.000 0.05, so the ratio of liquidity to solvency has a significant impact on stock prices. The t-value for the CR t-test is -0.799 1.674, and its significance level is 0.440 > 0.05. This demonstrates that the liquidity ratio has little effect on stock prices. The solvency ratio has a marginally significant impact on stock price, as evidenced by the DER value of 1.924>1.67412, which is based on a significant value of 0.04 0.05. At the same time, stock prices are significantly influenced by the liquidity to solvency ratio. The f-test results are 3.557> 3.17, a significant value of 0.000 0.05 that shows the liquidity ratio has no appreciable impact stock value